Le réseau social des maraîchers à abidjan agit sur la perception des préoccupations et des risques sanitaires liés à l’eau - Barbara Matthys; Francis A. Adiko; Guéladio Cissé (VertigO)
The purpose of the present study, carried out in market garden settings of Abidjan, Côte d’Ivoire, was to investigate the farmers’ main problems, their perceptions of illnesses and health risks, and how the latter are associated with the socio-economic status of the households, as well as the social cohesion of farming communities. The main problems identified include insecure land tenure and the paucity of bringing farm products to the local markets. Tiredness and a contaminated environment were the major health preoccupations. In the absence of sound health education and locally-adapted interventions, urban farmers do not attach sufficient importance to health risk prevention. We suggest that technical support, in concert with information, education and communication on health risk prevention, holds promise to enhance productivity, and hence improve the livelihoods of urban farmers in Abidjan.